(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The plastic parts having complex three dimensional structures are produced by Plastic injection molding system. The quality of the product is determined by controlling the temperature of the mold cavity. The mold cavity temperature control with the conventional ON/OFF, PI, and PID controllers have several disadvantages. This paper proposes the method to reduce settling time and undershoot in cavity temperature control with selected evolutionary algorithms. The controller parameters are optimized with Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) Algorithm for PID and I-PD controllers by considering Mean Square Error (MSE) as fitness function. Compared to conventional methods the parameter optimization using soft computing methods such as GA and PSO improves the performance indices of PID and I-PD controllers.